Conditions of teaching: new weavings of the assessment policy for quality - Elton Luiz Nardi; Marilda Pasqual Schneider (Universidade Federal de Santa Maria, 2014)
The article aims to analyze actions involving teaching, particularly those relating to the objective conditions of work and of employment, taking into account new weavings of policy evaluation for the quality of basic education involved in Ideb. It examines actions informed by school administrators and elementary school teachers, aiming at improving educational quality. Points out that, although many informed actions involve teachers' working conditions, the majority of them focuses on the material conditions and it was drawn taking Ideb as a mobilizing factor. It was concluded that the role the school is called to exercise focuses on producing results aiming national goals that have already asserted the difficult working conditions of teachers.